Kelimpahan Jenis Vektor di Peternakan Sapi Potong di Wilayah Perbatasan RI-RDTL, Kabupaten Belu - Christian, Dheaustyn Lilo Meisye; Almet, Julianty; Wuri, Diana Agustiani; Djungu, Dewi F. L. (Jurnal Veteriner Nusantara, 2025)
East Nusa Tenggara (NTT) is a province that borders directly with neighboring Timor Leste. Kakuluk Mesak is one of the sub-districts that borders directly with Timor Leste, the existence of the Mota'ain Cross Border Post (PLBN) which makes it easier for people to carry out trade activities, namely the sale of cattle and interaction between livestock is more vulnerable to the risk of spreading disease vectors on the border between countries. This study aims to determine the types of vectors found in beef cattle farms and the relative abundance on farms in the RI-RDTL border area, Belu Regency. The collection of fly samples used three methods, namely sweeping, manual and light trap methods, collection of mosquito samples using the light trap method and collection of ticks samples using the manual method. Fly sample preparation is done by piercing the fly body with a pinning needle at ⅓ of the thorax, mosquito sample preparation is done by attaching the sample to a triangular paper that has been pierced with a pinning needle, then for ticks samples that have been captured will then be put into a collection bottle that has been filled with 70% alcohol. The diversity of fly and mosquito species was analyzed using the relative abundance formula. The diversity obtained during the study was flies (Hippobosca sp., Stomoxys calcitrans and Musca domestica), mosquitoes (Aedes sp., and Culex sp.) and ticks (Boophilus microplus). Factors that play a role in the diversity of vector species are the availability of food, breeding places, temperature and humidity. The number of samples obtained during the study was 501 flies, 55 mosquitoes and 4 ticks.